1 Archives of Maryland 343 - (:unkn) unknown (My University, 1654)
"Noe work shall be done on the Sabboth day but that which is of Necessity and Charity to be done no Inordinate Recreations as fowling, fishing, hunting or other, no shouting of Gunns be used on that day Except in Case of Necessity
Keywords: SABBATH-BREAKING LAW